Truncation effects in an evacuated compound parabolic and involute concentrator with experimental and analytical investigations. (25th June 2018) - Ustaoglu, Abid; Okajima, Junnosuke; Zhang, Xin-Rong; Maruyama, Shigenao
Highlights: An ideal non-imaging concentrator was designed and experimentally tested. Optimum design geometry is decided for different truncation level of concentrator. The truncated concentrator is operated without significant reduction on performance. The experimental investigation shows good agreement with theoretical model. The truncated concentrator has advantages for economic viability and building app. Abstract: A two-stage line-axis solar concentrator composed of parabolic and involute reflectors with tubular absorber, have been designed and experimentally analyzed for thermal applications. The concentrator is covered by evacuated glass tube for low-heat loss configuration. Due to steep angle at the end of compound parabolic reflector, the concentrator tolerates to truncate a portion of the reflector with only slight reduction on the performance. Optimum truncation level is estimated by evaluating of ray acceptance, which is described as the ratio of aperture area of the concentrator to diameter of glass cover, concentration ratio, optical performance and thermal performance. The concentrator with truncation level of 50% shows preferable performance with only 1% reduction in thermal performance as well as significant reduction on material requirement. An experimental analysis was conducted for a 50% truncated concentrator to validate the ray tracing analysis and the thermal performance as a function of inlet temperature of water and the surface temperature of absorber. The experimental results show good agreement with the ray-tracing program written for theoretical evaluation. Consequently, the truncation of the concentrator provides requirement of less amount of optical component through significant reductions in size of reflector and glass cover with a small reduction in concentrator rate to achieve the economic viability and attraction for buildings.